Sport, recreation and juvenile crime : an assessment of the impact of sport and recreation upon Aboriginal and non-Aboriginal youth offenders - Mason, Gail, 1962-; Wilson, Paul R. (Paul Richard), 1941-; Australian Institute of Criminology (Canberra : Australian Institute of Criminology, 1988)
An assessment of the impact of sport and recreation upon Aboriginal and non-Aboriginal youth offenders.
Bibliography: p. 169-182.
Keywords: Recreation and juvenile delinquency -- Australia; Juvenile delinquency -- Australia -- Prevention; Youth, Aboriginal Australian -- Legal status, laws, etc; Juvenile delinquents -- Rehabilitation -- Australia; Sports -- Australia; Law enforcement - Criminal law and procedure; Crime; Sport; Australia